Construction of a 3D rGO–collagen hybrid scaffold for enhancement of the neural differentiation of mesenchymal stem cells. Issue 4 (11th January 2016) - Guo, Weibo; Wang, Shu; Yu, Xin; Qiu, Jichuan; Li, Jianhua; Tang, Wei; Li, Zhou; Mou, Xiaoning; Liu, Hong; Wang, Zhonglin
Abstract : The PADM–rGO hybrid scaffold is a promising candidate for nerve regeneration, which can not only support the adhesion and proliferation of MSCs but also can enhance the cells neural differentiation. Abstract : The cell–material interface is one of the most important considerations in designing a high-performance tissue engineering scaffold because the surface of the scaffold can determine the fate of stem cells. A conductive surface is required for a scaffold to direct stem cells toward neural differentiation. However, most conductive polymers are toxic and not amenable to biological degradation, which restricts the design of neural tissue engineering scaffolds. In this study, we used a bioactive three-dimensional (3D) porcine acellular dermal matrix (PADM), which is mainly composed of type I collagen, as a basic material and successfully assembled a layer of reduced graphene oxide (rGO) nanosheets on the surface of the PADM channels to obtain a porous 3D, biodegradable, conductive and biocompatible PADM–rGO hybrid neural tissue engineering scaffold. Compared with the PADM scaffold, assembling the rGO into the scaffold did not induce a significant change in the microstructure but endowed the PADM–rGO hybrid scaffold with good conductivity. A comparison of the neural differentiation of rat bone-marrow-derived mesenchymal stem cells (MSCs) was performed by culturing the MSCs on PADM and PADM–rGO scaffolds in neuronal culture medium, followed by the determination of gene expression and immunofluorescence staining. The results of both the gene expression and protein level assessments suggest that the rGO-assembled PADM scaffold may promote the differentiation of MSCs into neuronal cells with higher protein and gene expression levels after 7 days under neural differentiation conditions. This study demonstrated that the PADM–rGO hybrid scaffold is a promising scaffold for neural tissue engineering; this scaffold can not only support the growth of MSCs at a high proliferation rate but also enhance the differentiation of MSCs into neural cells.